Kopling Oksidatif Eugenol Menggunakan Ekstrak Enzim Peroksidase dari Akar Tanaman Sawi Hijau serta Uji Bioaktivitasnya - Ardiansah, Bayu; Cahyana, Antonius Herry; Suwarso, Wahyudi Priyono; Maryana, Rianti; Merly, Siti (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2017)
Peroxidase has been successfully extracted and partially purified from Brassica juncea L. Czern root with protein content and specific activity of 0.747 mg/mL and 0.244 U/mg, respectively. Then, it was applied as biocatalyst for green oxidative coupling reaction of eugenol to produce an orange crystal, dimeric form of eugenol (84% yield). Structure elucidation was done by using FTIR, UV-Vis and GC-MS instruments. The optical activity of dimeric eugenol was found to have Ra-configuration. Furthermore, biological activity of the product as antioxidant has been evaluated resulting in IC50 values of 32.14 and 42.43 ppm for dimeric and monomeric eugenol, respectively.